Timing of gestational diabetes diagnosis, gestational weight gains and offspring growth trajectory: a prospective birth cohort study - Xiao-guang Yin; Peng Wang; Mei-ting Zhou; De-qin Li; Rui-xue Tao; Fang-biao Tao; Yang Wang; Peng Zhu (BMC, 2023)
Abstract Background The evidence on the associations of the timing of maternal gestational diabetes mellitus (GDM) with the comprehensive growth trajectory from perinatal to early childhood in offspring is limited. The potential mechanism remains elusive. Our aim is to estimate the associations of the timing of GDM diagnosis and gestational weight gains (GWG) with the growth trajectory of children from perinatal to early childhood. Methods A total of 7609 participants are included from the Maternal & Infants Health in Hefei cohort study. Primary predictors were the timing of maternal GDM diagnosis and GWG during pregnancy. The main outcomes included fetal ultrasonic measurements, birth size as well as BMI peak indicators during infancy within 48 months. Results GDM diagnosed before 26 weeks was associated with increased risks of overgrowth for fetal abdominal circumference (OR 1.19, 95% CI 1.04-1.36) and birth weight (OR 1.51, 95% CI 1.19-1.91) when compared with unexposed. GDM diagnosis < 26 weeks was related to the higher BMI peak (β 0.16, 95%CI 0.03-0.28) within 48 months. The significantly additive impacts of maternal early GDM diagnosis and excessive gestational weight gains (EGWG) on offspring overgrowth were observed. Women in GDM < 26 weeks with early EGWG group had higher levels of hsCRP compared with GDM > 26 weeks (P < 0.001). Conclusions Exposure to maternal GDM diagnosed before 26 weeks with early EGWG could lead to shifts and/or disruptions from the typical growth trajectory from perinatal to early childhood in offspring.